Synthetic anticonvulsants, antihypoxic agents, and inducers of the liver monooxygenase system; XIX; The synthesis, anticonvulsive, and antihypoxic properties of benzhydrylamine carboxylates; Pharmaceutical Chemistry Journal; Vol. 28, iss. 3 - Tignibidina А. S.; Bakibaev A. A. Abdigali Abdimanapovich; Gorshkova V. K.; Saratikov A. S.; Krauin'sh M. P. (1994, 1994)
Title screen